“The Old Man of a Sacred Town”: Ancient and Recent Representations of a Bear-like Deity - A. V. Baulo; А. В. Бауло (IAET SB RAS, 2016)
Native northwestern Siberian representations of a bear-like deity known as the Old Man of a Sacred Town span the period from the Early Iron Age to the present. It is proposed that the character standing full-length is indeed the deity, whereas bears shown in side view or in so-called sacrifi cial posture (head between fore paws) refer to prey. The distinction was especially marked in Early Iron Age representations found on the right-bank stretch of the Ob from its confl uence with the Irtysh in the south to Vanzevat village near Beloyarsk, Khanty-Mansi Autonomous District–Yugra, in the north. Certain newly acquired Oriental and Sarmatian bronze mirrors and silver artifacts, too, depict bears standing full-length; the scene shown on one of the mirrors is paralleled by ethnographic evidence. In the 19th and 20th centuries, bear festivals were held by several local groups of Ob Ugrians, specifi cally in a territory Eva Schmidt considers the source and the secondary area of the Old Man’s cult. These rites played a key role in the center of the Por clan—the Vezhakary village near Beloyarsk, the Khanty-Mansi Autonmous District–Yugra. During the rite, the killed bear is placed in the “ancient” sacred posture, its head between the fore paws. This posture, however, is not represented in Mansi or Khanty art, where the “Old Man of the Sacred Town” is still being rendered standing full-length.